Cultivation Analysis of Toxic Gamer Attitudes in Gaming Youtuber Content : (Analysis of the Effect of Media Content Cultivation on the Oura Gaming Channel) - Aripin, Zaenul; Purwasito, Andrik; Hastjarjo, Sri (COMMICAST, 2025)
The popularity of the game Mobile Legends: Bang Bang (MLBB) among Indonesian teenagers has encouraged many content creators to upload videos on social media platforms such as YouTube. One of the leading creators is Oura Gaming, a gaming YouTuber with 8.2 million subscribers. This large number of subscribers indicates that many people enjoy the content presented. However, most of the uploaded videos contain toxic elements that serve as entertainment for young viewers, potentially influencing their behavior in social interactions. This study aims to analyze Oura Gaming's YouTube content consumption patterns using Gerbner's cultivation theory, which emphasizes the role of mainstreaming and resonance in shaping individual social experiences. This research uses a qualitative method with a phenomenological approach to explore individuals' experiences after watching content containing toxic messages. Participants consisted of two students who were active MLBB players and loyal viewers of Oura Gaming.  The results showed that both participants had high viewing intensity, enjoyed the aggressiveness and toxic elements in the content, and tended to imitate the toxic language they watched in their daily social interactions. These findings indicate that the consumption of negatively charged content can affect individuals' communication patterns and social behavior. This research contributes to the understanding of the impact of digital media on adolescent behavior and provides insights for digital literacy policy development.